2016
DOI: 10.1371/journal.pgen.1006012
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Sequence Evolution and Rare Homoeologous Conversion in Tetraploid Cotton

Abstract: Allotetraploid cotton species are a vital source of spinnable fiber for textiles. The polyploid nature of the cotton genome raises many evolutionary questions as to the relationships between duplicated genomes. We describe the evolution of the cotton genome (SNPs and structural variants) with the greatly improved resolution of 34 deeply re-sequenced genomes. We also explore the evolution of homoeologous regions in the AT- and DT-genomes and especially the phenomenon of conversion between genomes. We did not fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 47 publications
3
34
1
1
Order By: Relevance
“…1a ; Additional file 8 : Dataset 1). The subsequently produced neighbor-joining (NJ) tree resulted in two largely divergent clades: the G. hirsutum clade ( n = 85) and the G. barbadense clade ( n = 52), consistent with a previous study, although with a limited number of accessions [ 23 ]. Both studies suggested a strong divergence between G. hirsutum and G. barbadense .…”
Section: Resultssupporting
confidence: 86%
“…1a ; Additional file 8 : Dataset 1). The subsequently produced neighbor-joining (NJ) tree resulted in two largely divergent clades: the G. hirsutum clade ( n = 85) and the G. barbadense clade ( n = 52), consistent with a previous study, although with a limited number of accessions [ 23 ]. Both studies suggested a strong divergence between G. hirsutum and G. barbadense .…”
Section: Resultssupporting
confidence: 86%
“…During rediploidization, pseudogenized genes lost function, or underwent sub-functionalization to partition ancestral gene function, or neo-functionalization to obtain a new function [ 57 , 58 , 60 , 63 ]. Two paralogs generally showed a dominant, biased or silencing expression pattern [ 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 ]. In this study, we revealed a significantly biased expression of Eccxcr4a and Ec_cxcr4b in adult tissue, gonads and embryos at different stages.…”
Section: Discussionmentioning
confidence: 99%
“…GWAS have been used to analyze millions of genetic variants among the genomes of several individuals to unravel genotype-phenotype associations, genetics of fiber quality and yield, and environmental adaptation-related traits [8,18,25,37,39]. GhFL1, GhFL2, and GhXIK were found to be involved in fiber cell elongation, and a chaperone DnaJ-domain superfamily gene (Gh_A07G1769) was shown to be related to fiber strength.…”
Section: Gwas In Cottonmentioning
confidence: 99%